CHINA’S MARKETING STRATEGY IN THE TRADE WAR ERA: CASE STUDY - EXPANSION OF XIAOMI INC. TO INDONESIA - Ganang Adikarya Muhammad, Dini Septyana muhammad (: 2621-0924)
AbstractThis study discuss how China's and Xiaomi's strategy to achieve its interests in a trade war. This study analyzes how effective China's strategies to exploite the opportunity for ACFTA in Indonesia use the library method based on existing data it includes the concepts of economic liberalization and MNCs. To tackle the trade war, maximum attention and strategy are needed. Therefore, the Chinese government made an economic cooperation agreement on the ASEAN-China Free Trade Area (ACFTA) with the countries in the ASEAN region. With certain strategies carried out by the Chinese government and Xiaomi, China can win a trade war with the United States and become the highest economy in the world.Keywords: Trade war, China, Xiaomi, ACFTA, Foreign direct investment